Prispevek k poznavanju favne pajkov skakačev v Sloveniji (Araneae, Salticidae) - Fišer, Cene (Natura Sloveniae, 2001)
The material from Biological Department animal collection (Biotehnical Faculty, University of Ljubljana) and the material collected and filed during recent years was revised. 21 species of jumping spiders (Salticidae) new for Slovenia were found: Asinellus festivus (C.L. Koch, 1834), Euophrys herbigrada(Simon, 1871), Evarcha michailovi Logunov, 1992, Chalcoscirtus inflmus (Simon, 1868), Heliophanus aeneus (Hahn, 1932), H. dubius C.L. Koch, 1835, H. kochii Simon, 1868, H. melinus L. Koch, 1867, H. patagiatus Thorell, 1875, H. tribulosus Simon, 1868, Icius hamatus (C.L. Koch, 1846), Marpissa pomatia (Walckenaer, 1802), Mendoza canestrinii (Ninni, 1868), Neon rayi (Simon, 1875), Pellenes nigrociliatus (Simon, 1875), Pellenes seriatus (Thorell, 1875), Pseudicius encarpatus (Walckenaer, 1802), Pseudeuophrys erratica (Walckenaer, 1826), Synagales hilarulus (C.L. Koch, 1846), Synageles venator (Lucas, 1836) and Talavera thorelli (Klucrynski, 1891). The large number of new spider species for Slovenia indicates that Slovenian araneofaunais poorly known.
Keywords: Arachnida; Classification; Ecosystem; Ekosistem; Pajki; Spiders